Analisis Pendapatan Petani Kakao di Desa Makmur Kecamatan Palolo - Muhammad Idfal; Rita Yunus; Laendatu Paembonan; Santi Yunus; Ika Rafika (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to analyze cocoa farming income in Makmur Village, Palolo District, Sigi Regency, Central Sulawesi Province. This research was conducted in Makmur Village, Palolo District, Sigi Regency, Central Sulawesi Province in September 2023 - January 2024. Primary data was obtained from surveys and interviews using questionnaires with cocoa farmers as respondents and secondary data was obtained from literature and related institutions/agencies. The data analysis used is farming income analysis. The results of the income analysis of cocoa farmers in Makmur Village, Palolo District show that the average income of cocoa farmers in their farming business is IDR 29,551,909 per year/ha, the average expenditure from cocoa farmers' production costs is IDR 3,757,318 per year/ha, and the average -The average income from farming in Makmur Village is IDR 25,794,591 per year/ha. And the R/C from cocoa farmers' results is 7.87. The marketing channel for cocoa farmers in Makmur Village is farmers as producers → then sold to collectors in the village at a price of IDR 57,000 per kg. Collecting traders also provide a prime of IDR 1,000 per kg. Therefore, the more dry cocoa produced to be deposited with collectors, the more prime will be received and the prime will be received after 6 months of deposit. The government's role in efforts to increase production and income of cocoa farmers in Makmur Village, Palolo District, Sigi Regency, Central Sulawesi Province, namely the Village Government, the Central Sulawesi Provincial Agriculture Service and the Sigi Regency Government carry out training and extension activities using a group approach. With assistance and training from the government to encourage farmers so that production of cocoa plants in Makmur Village can increase so as to provide benefits in the form of income to cocoa farmers in Makmur Village, Palolo District.